2022
DOI: 10.1002/hep4.2037
|View full text |Cite
|
Sign up to set email alerts
|

Activin B promotes the initiation and progression of liver fibrosis

Abstract: The role of activin B, a transforming growth factor β (TGFβ) superfamily cytokine, in liver health and disease is largely unknown. We aimed to investigate whether activin B modulates liver fibrogenesis. Liver and serum activin B, along with its analog activin A, were analyzed in patients with liver fibrosis from different etiologies and in mouse acute and chronic liver injury models. Activin B, activin A, or both was immunologically neutralized in mice with progressive or established carbon tetrachloride (CCl … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We further experimentally validated that activins A and B promote HSC activation in vitro. It was recently shown that both hepatic and circulating activin B are increased in patients with MASH and alcoholic cirrhosis, and neutralizing activin B with antibodies largely prevented liver fibrosis in the CCl 4 -induced liver injury mouse model ( 39 ). Another recent study indicated that activin A can activate HSCs indirectly by inducing TNFα and TGFβ in Kupffer cells (liver macrophages) ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…We further experimentally validated that activins A and B promote HSC activation in vitro. It was recently shown that both hepatic and circulating activin B are increased in patients with MASH and alcoholic cirrhosis, and neutralizing activin B with antibodies largely prevented liver fibrosis in the CCl 4 -induced liver injury mouse model ( 39 ). Another recent study indicated that activin A can activate HSCs indirectly by inducing TNFα and TGFβ in Kupffer cells (liver macrophages) ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis was induced by 10 mL/kg intraperitoneal injections of 1:10 diluted carbon tetrachloride (CCl 4 ) (Sigma Aldrich, St. Louis, MO, USA) in corn oil twice weekly for a total of 6 to 9 weeks for chronic studies [28]. For acute studies, tissues were harvested 6, 24, or 48 h following a single injection of CCl 4 .…”
Section: Carbon Tetrachloride Liver Fibrosis Modelmentioning
confidence: 99%
“…Therefore, the factors that induce CAF phenotype and its molecular targets in GC still need to be fully studied. Because activin B has been proved to be pleiotropic in a variety of inflammatory diseases and fibrosis [ 10 , 19 , 20 ], our research purpose focus on the possible role of INHBB in GC development and its potential contribution to microenvironment crosstalk.…”
Section: Introductionmentioning
confidence: 99%